Estrategia comunicacional de las campañas electorales en medios digitales de las listas #35 y #6 en la ciudad de Babahoyo elecciones febrero 2019 - Gómez Roca, Maria de Los Angeles (2020)
In this project, the definition of strategy, communication strategy, political communication and political propaganda is analyzed, based on the criteria of authors such as Quinn, Alejandro Pizarroso; as well as the history of two political parties in Ecuador; trying to be as concretely as possible in each one. He maintains that the communication strategy is a guide that compiles the resources that communication has in a long-term pattern or model, according to the objectives already established by the company or institution. In addition, he argues that the political communication strategy is the model or guide that a political group designs with the resources it has to present its proposal for long-term work according to the objectives that have been previously raised to obtain credibility, scope and acceptance in a variable and demanding society; same that can be presented in different media; radio, press, television, social networks, etc. He also maintains that political propaganda sells a political character or a political image; and it does so through the different means of communication that exist today; and they can be written press, television, social networks, radio, etc. Which depends on the plan that has been proposed, on the economic possibilities, and on the social group that you want to reach. The Country Alliance Movement, list 35; It serves as a political organization for the Citizen Revolution promoted by economist Rafael Correa, it is formed by more than 30 political and social organizations; Of which we can highlight: Country Movement, Democratic Action, Alfarista Bolivarian Alliance, Ecuadorian Socialist Party, Rupture of the 25, etc.